2023
DOI: 10.3171/2022.4.jns212369
|View full text |Cite
|
Sign up to set email alerts
|

Compactness index: a radiosurgery outcome predictor for patients with unruptured brain arteriovenous malformations

Abstract: OBJECTIVE The goal of the study was to define and quantify brain arteriovenous malformation (bAVM) compactness and to assess its effect on outcomes after Gamma Knife radiosurgery (GKRS) for unruptured bAVMs. METHODS Unsupervised machine learning with fuzzy c-means clustering was used to differentiate the tissue constituents of bAVMs on T2-weighted MR images. The percentages of vessel, brain, and CSF were quantified. The proposed compactness index, defined as the ratio of vasculature tissue to brain tissue, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…We could not determine whether the independent factors for post-SRS hemorrhage reflect the natural history of bAVMs or the effects of radiosurgery. However, previous analysis showed that bAVM volume and morphology significantly correlated with complete obliteration after radiosurgery 13 . Since obliteration of bAVMs substantially alter the hemorrhage risk, the predictors found in the current study less likely reflected the natural bleeding tendency, but could serve as a guidance for patient selection for management of unruptured bAVMs.…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…We could not determine whether the independent factors for post-SRS hemorrhage reflect the natural history of bAVMs or the effects of radiosurgery. However, previous analysis showed that bAVM volume and morphology significantly correlated with complete obliteration after radiosurgery 13 . Since obliteration of bAVMs substantially alter the hemorrhage risk, the predictors found in the current study less likely reflected the natural bleeding tendency, but could serve as a guidance for patient selection for management of unruptured bAVMs.…”
Section: Discussionmentioning
confidence: 76%
“…The independent effect of the margin dose could be due to faster obliteration process with higher radiation dose level, which shortened the latency period of bAVMs receiving SRS 30 , 31 ; alternatively, it could reflect that the whole bAVMs were completely covered in a certain level of radiation dose. However, previous studies have demonstrated a positive correlation between the incidence of radiologic or permanent RICs and prescribed dose 13 , 24 , 32 . The benefit of dose escalation should be weighed against radiation-induced side effects.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations